Dimensions of Conspiracy : An inquiry into the cognitive and epistemic standing of conspiracy theories - Tsapos, Melina (Department of Philosophy, Lund University, 2025)
This doctoral thesis investigates the conceptual, epistemological, and psychological dimensions of conspiracy theories, aiming to develop a more precise and philosophically rigorous framework for understanding and evaluating them. The work is structured around five original papers that address key questions: What constitutes a conspiracy theory? Are such theories inherently irrational? How should we conceptualize their epistemic status in light of expert testimony, trust, and cognitive psychology? The thesis begins by examining the contested nature of the term conspiracy theory, revealing the limitations of both pejorative and overly broad definitions. It engages with the philosophical debate between generalism and particularism, arguing for a neutral, theoretically useful definition based on Carnapian conceptual engineering. It then explores whether belief in conspiracy theories can be rational, with attention to decision-theoretic considerations and the epistemic role of experts. The final chapter investigates why individuals come to endorse conspiracy theories, evaluating claims that such beliefs are primarily driven by irrationality, cognitive biases, or social belonging. A central contribution is the development of the Dimensions framework—a descriptive tool for analysing conspiracy theories not solely in terms of truth or falsity, but with attention to the contexts, motivations, and epistemic norms surrounding their adoption. This framework enables a more nuanced understanding of conspiracy theories as complex social phenomena. By combining conceptual analysis, epistemological evaluation, and psychological insight, the thesis offers a comprehensive and interdisciplinary approach that contributes to ongoing debates in conspiracy theory theory—the academic study of conspiracy theories—as well as to social epistemology more broadly.
Keywords: conspiracy theory; experts; critikal thinking; probability; social epistemology; conceptual engineering